Introduction to reference work - Katz, William A. (McGraw-Hill, 1992)
The ten chapter in Volume II are divided into 3 parts: Part One, " Informationn and the community," contain two chapters to familiarize readers with various group in the community, their information and reference needs, and how professional attempt to serve those needs. Part Two, " Interview and Search," devotes Chapter 3 through 6 to the vital task of explaining how to isolate and understand the questions readers put to the librarians as well as basic methods to finding the correct answer(s). The emphasis is on practical application of tried and true methods of interviewing and searching. Attention is given both manual and computer searches. Part Three, " Library Instruction, Networks, Policies, and Evaluation," is comprise of the last four chapters and covers the activities of reference librarians when not responding to dicrect questions.